Pandangan Hukum Islam Tentang Jual Beli Parfum Beralkohol (Studi Kasus Di Toko Parfum Effiel Kecamatan Karangpawitan Kabupaten Garut) - Sunarsa, Sasa; Rimosan, Mochammad Thantowi Jauhari (Jurnal Hukum Ekonomi Syariah, 2023)
Perfume or perfume is one type of cosmetics loved by humans. Especially women, in order to create comfort in associating with others. However, in this case most perfumes traded in the market contain alcohol which is used as a solvent (solvent). Whereas in Islamic law, alcohol is one of the substances that are forbidden because of the effects it causes. From this problem, the compiler is interested in examining the law of buying and selling perfumes containing alcohol in terms of Islamic law, especially in terms of how the implementation of buying and selling alcoholic perfumes and what alcohol.. This research is included in the type of qualitative research with the collection techniques used, namely interviews, observation and documentation. From the data is analyzed through the stages of data reduction, data presentation, then conclusions. Based on the results of this study, it was found that the Islamic legal view of the process of buying and selling alcoholic perfumes, has fulfilled the pillars and conditions, in the contract of buying and selling, so that the law according to Islamic law is permissible As long as the alcohol content in the perfume does not cause a drunken effect on the user or people nearby, the perfume can be traded. In the Qur'an and Hadith studied by the author that in the use of alcoholic or non-alcoholic perfumes there is no statement about the certainty to say haram in using it, in other words it can be used as in the hadiths of the Prophet that have been put forward based on the intention and purpose possessed. Keywords : Islamic Law, Buying and Selling, Alcoholic Perfumes